Effect of orthodontic management and orofacial muscle training protocols on the correction of myofunctional and myoskeletal problems in developing dentition. A systematic review and meta‐analysis. (27th August 2018) - Koletsi, Despina; Makou, Margarita; Pandis, Nikolaos
Abstract: The aim of this review was to evaluate available evidence on the effect of early orthodontic management and myofunctional treatment in the developing dentition children, on anterior open bite correction, as well as on normalization of patterns of mouth breathing, swallowing and tongue resting position and pressure. Electronic searches in MEDLINE, Cochrane and LILACS, without language restrictions were conducted. Additionally, unpublished literature was identified. Randomized controlled trials, or controlled clinical trials, comparing interventions applied to manage anterior open bite and other muscle functions such as breathing/swallowing pattern and tongue resting position and pressure, were considered. Quality assessment was based on the Cochrane Risk of Bias tool. Random effects meta‐analyses were conducted to assess treatment effects. From the 265 initial search results, 15 articles were included in the review. Eight were randomized controlled trials (RCTs) and 7 were controlled clinical trials. Treatment outcomes comprised skeletal and dentoalveolar changes recorded cephalometrically, mouth posture and lip closure normalization, improvement of tongue resting position/pressure and modification of swallowing pattern. Quantitative synthesis was possible for only 2 of the included RCTs. There was no evidence to support bonded lingual spurs over banded fixed appliances for the correction of anterior open bite in mixed dentition children presenting nonnutritive oral habits at the onset of treatment (SMD: −0.03; 95%CI: −.81, 0.74; P  = 0.94). Although early orthodontic management and myofunctional treatment in the deciduous and mixed dentition children appears to be a promising approach, the quality of the existing evidence is questionable.